Motif Warm-glow dan Kepuasan Petani Berusahatani Organik: Kasus di Pulau Jawa - Muntoro Muntoro; Irham Irham; Jangkung Handoyo Mulyo; Any Suryantini (Universitas Islam Kadiri, 2022)
The main objective of developing organic agriculture should not deviate from the principles of organic agriculture which include economics, health and the environment. However, there is often a trade off between the three main objectives. It was found that organic farmers in developed countries prioritize non-economic goals such as health and environmental sustainability. And vice versa with organic farmers in developing countries. However, there are a few organic farmers in developing countries who still survive, coming from indigenous peoples or ethnic groups who are considered backward. This is because there is a warm-glow motif which is interpreted as happiness and pleasure in doing good.